Prevalence, characteristics, and morphology of supernumerary teeth among patients visiting a dental institution in Rajasthan - Pulkit Khandelwal; A Bhagavandas Rai; Bipin Bulgannawar; Neha Hajira; Abhijeet Masih; Arvind Jyani (Wolters Kluwer Medknow Publications, 2018)
Context: Supernumerary teeth/tooth (ST) is a developmental anomaly of dentition. Variation in developmental and eruption pattern of ST can lead to the development of numerous complications in oral cavity. Aim: The aim of this study was to investigate prevalence, characteristics, and morphology of ST among patients visiting a dental institution in Rajasthan, India. Materials and Methods: During 1-year study, clinical examination of 9248 participants was performed. Morphology, type, location, number, position of eruption, state of eruption of ST, and associated complications were determined. Correlations between location of ST based on position of eruption, state of eruption, and associated complications were also determined using Chi-square test. Results: The frequency of presence of ST in the studied population was 0.63% (58 participants). In these 58 participants, eighty-two supernumeraries were found. Forty-six participants (79.32%) presented with one ST. Males were more affected than females (2.05:1), and the maxilla was the most commonly affected region. Among 82 identified supernumeraries, we noted highest incidence of parapremolars (39.02%) and conical morphology (46.35%). The most common position of eruption was normal (68.30%) and most of these 82 teeth were erupted in oral cavity (57.31%). These ST have led to various endodontic, orthodontic, periodontal, and other complications in the studied population. The relation of varying complications with different location of supernumerary was found to be highly significant (P = 0.000). Conclusion: ST are best detected and diagnosed by thorough clinical examination and radiographic investigation. Early detection and adequate treatment plan should eradicate the potential future complications caused by ST.